Preseismic groundwater level changes induced by crustal deformations related to earthquake swarms off the east coast of Izu Peninsula, Japan - Koizumi, Naoji; Kitagawa, Yuichi; Matsumoto, Norio; Takahashi, Makoto; Sato, Tsutomu; Kamigaichi, Osamu; Nakamura, Koji (Geophysical research letters, 2004)
Groundwater level changes since October 1994 of Omuroyama‐kita (OMR) well in Izu Peninsula, Japan, were examined in relation to six earthquake swarms with which large crustal deformations were accompanied. After removing not only tidal and barometric effects but rainfall effect on groundwater, we detected four preseismic groundwater level changes accompanied with crustal deformations recorded at nearby stations. Those groundwater level changes are interpreted to have caused by crustal deformations or volumetric strain changes which seem to be caused by dike intrusions, which are possible sources of the earthquake swarms off the east coast of Izu Peninsula.